2010
DOI: 10.12968/bjon.2010.19.5.47058
|View full text |Cite
|
Sign up to set email alerts
|

The use of advanced physical assessment skills by cardiac nurses

Abstract: Cardiac nurses selectively use physical assessment skills, predominately related to the cardiorespiratory systems. Organisational structure, professional relationships and the professionalism of the individual nurse appear to play a significant part in the use of physical assessment skills. Although the findings from this qualitative study cannot be generalized, they concur with findings from recent research into physical assessment skills used by a variety of UK nurses. The implications identified are: first,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Factors that might have influenced the competency and frequency of perormance need further investigation. Edmunds, Ward and Barnes (2010) pointed that the use of assessment skill is not only the matter of educational preparations but the professionalism that individual nurses have. In their study, nurses with broader and clearer views of nursing utilized more assessment skills.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that might have influenced the competency and frequency of perormance need further investigation. Edmunds, Ward and Barnes (2010) pointed that the use of assessment skill is not only the matter of educational preparations but the professionalism that individual nurses have. In their study, nurses with broader and clearer views of nursing utilized more assessment skills.…”
Section: Discussionmentioning
confidence: 99%
“…The skills used also depend on nurses' areas of specialty. [16,[19][20][21] Cicolini [18] reported that nurses working in intensive care units or nursing homes are more likely to use physical assessment skills than nurses in other settings.…”
Section: Introductionmentioning
confidence: 99%
“…Programme curricula noted to have a huge amount of physical assessment content however, demand that choices be made about what is actually taught (Giddens, 2007;Secrest, Norwood, & Dumont, 2005). Some studies of nursing curricula distinguish between physical assessment skills and advanced physical assessment skills, suggesting that selective skills may be used in particular contexts (Edmunds, Ward, & Barnes, 2010;Lesa & Dixon, 2007). Influenced by practice setting and patient population, cardiac nurses mainly use skills related to the cardiac system (Edmunds et al, 2010) while the curricula of nurse practitioners demands teaching of advanced practice physical assessment skills (Kelley, Kopac, & Rosselli, 2007;Price, Han, & Rutherford, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of nursing curricula distinguish between physical assessment skills and advanced physical assessment skills, suggesting that selective skills may be used in particular contexts (Edmunds, Ward, & Barnes, 2010;Lesa & Dixon, 2007). Influenced by practice setting and patient population, cardiac nurses mainly use skills related to the cardiac system (Edmunds et al, 2010) while the curricula of nurse practitioners demands teaching of advanced practice physical assessment skills (Kelley, Kopac, & Rosselli, 2007;Price, Han, & Rutherford, 2000). This situation suggests that given time pressures on undergraduate programme teaching hours, the skills that are required of generalist nurses in practice should be given priority in this curriculum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation